Dietary fiber pectin: challenges and potential anti-inflammatory benefits for preterms and newborns - Donadio, Janaina L. S.; Fabi, João Paulo; Sztein, Marcelo B.; Salerno-Gonçalves, Rosângela (Frontiers in Nutrition, 2024)
Pectins, a class of dietary fibers abundant in vegetables and fruits, have drawn considerable interest due to their potential anti-inflammatory properties. Numerous studies have indicated that incorporating pectins into infant formula could be a safe strategy for alleviating infant regurgitation and diarrhea. Moreover, pectins have been shown to modulate cytokine production, macrophage activity, and NF-kB expression, all contributing to their anti-inflammatory effects. Despite this promising evidence, the exact mechanisms through which pectins exert these functions and how their structural characteristics influence these processes remain largely unexplored. This knowledge is particularly significant in the context of gut inflammation in developing preterm babies, a critical aspect of necrotizing enterocolitis (NEC), and in children and adults dealing with inflammatory bowel disease (IBD). Our mini review aims to provide an up-to-date compilation of relevant research on the effects of pectin on gut immune responses, specifically focusing on preterms and newborns. By shedding light on the underlying mechanisms and implications of pectin-mediated anti-inflammatory properties, this review seeks to advance our knowledge in this area and pave the way for future research and potential therapeutic interventions.